2012
DOI: 10.1051/0004-6361/201117680
|View full text |Cite
|
Sign up to set email alerts
|

Ram pressure stripping of the multiphase ISM and star formation in the Virgo spiral galaxy NGC 4330

Abstract: It has been shown that the Virgo spiral galaxy NGC 4330 shows signs of ongoing ram pressure stripping at multiple wavelengths. At the leading edge of the interaction, the Hα and dust extinction curve sharply out of the disk. On the trailing side, a long Hα/UV tail has been found which is located upwind of a long Hi tail. We complement the multiwavelength study with IRAM 30m HERA CO(2-1) and VLA 6 cm radio continuum observations of NGC 4330. The data are interpreted with the help of a dynamical model including … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 31 publications
15
62
0
Order By: Relevance
“…14-24 and references therein). Recent detailed observations of ongoing gas depletion from galaxies in clusters are presented by the Very Large Array survey of neutral hydrogen (HI) in Virgo galaxies showing long tails of stripped gas behind galaxies, where the gas clumps in the tails are accelerated by ram pressure, leaving behind streams of new stars (22,24). Long tails of HI and ionized gas are observed in galaxies in several nearby clusters, consistent with the description given here (e.g., refs.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…14-24 and references therein). Recent detailed observations of ongoing gas depletion from galaxies in clusters are presented by the Very Large Array survey of neutral hydrogen (HI) in Virgo galaxies showing long tails of stripped gas behind galaxies, where the gas clumps in the tails are accelerated by ram pressure, leaving behind streams of new stars (22,24). Long tails of HI and ionized gas are observed in galaxies in several nearby clusters, consistent with the description given here (e.g., refs.…”
supporting
confidence: 85%
“…Long tails of HI and ionized gas are observed in galaxies in several nearby clusters, consistent with the description given here (e.g., refs. 21,22,[25][26][27].…”
mentioning
confidence: 99%
“…The timestep of interest (26 Myr) is marked by "model". (Vollmer et al 2008b) and NGC 4330 (Vollmer et al 2012a): we assume that the molecular fraction depends linearly on the square root of the gas density f mol = M mol /M tot = ρ/(0.03 M pc −3 ) and the molecular fraction cannot exceed unity. A detailed motivation for this prescription is given in Vollmer et al (2008b).…”
Section: Gas Distributionmentioning
confidence: 99%
“…To calculate the large-scale regular magnetic field for our simulations, we apply the same procedure as Otmianowska-Mazur & Vollmer (2003) and Vollmer et al (2012a). We solve the induction equation:…”
Section: Modelmentioning
confidence: 99%
“…These authors have shown that the molecular gas phase, even in high-density regions, can be removed during the interaction. Whereas detailed multifrequency observations of representative objects in nearby clusters begin to show cases of ongoing molecular gas ram pressure stripping events (Vollmer et al 2008a(Vollmer et al , 2009(Vollmer et al , 2012aSivanandam et al 2010), strong and convincing statistical evidence is still lacking. Since star formation occurs mainly inside molecular clouds, the perturbation of the molecular gas phase in any kind of interaction can have a strong impact on the evolution of the stellar populations of galaxies.…”
Section: Introductionmentioning
confidence: 99%